Eigenspectra Versus Eigenfaces: Classification with a Kernel-Based Nonlinear Representor - Liu, Benyong; Zhang, Jing (Advances in Natural Computation, 2005)
This short paper proposes a face recognition scheme, wherein features called eigenspectra are extracted successively by the fast Fourier transform (FFT) and the principle component analysis (PCA) and classification results are obtained by a classifier called kernel-based nonlinear representor (KNR). Its effectiveness is shown by experimental results on the Olivetti Research Laboratory (ORL) face database.